Nitrogen and Phosphorus Removal in Lab-Scale Activated Sludge Systems - Sarioglu, M.; Karakus, B.; Cebeci, Y. (Asian Journal of Chemistry, 2010)
The phenomenon of anoxic phosphate uptake with simultaneous denitrification was studied. Experiments have been carried out with biological nutrient removal in a single sludge system by using the activated slude samples from the modifications of nutrient removal activated sludge systems. The lab-scale reactor allows nitrification, denitrification and phosphorus removal alternatively by adding anaerobic, anoxic zone prior to activated sludge system. The aim of the study was to evaluate the denitriication behaviour in biological excess phosphorus removal activated sludge systems. Based on experimental study, the performance of the system for the KOI, NH4 and phosphorus parameters was reported. The study indicates that a significant fraction of the polyphosphorus organisms can be used as an electron acceptor in the absence of oxygen for oxidation of stored PHB and simultaneous uptake of phosphorus.